2023
DOI: 10.1371/journal.pone.0291734
|View full text |Cite
|
Sign up to set email alerts
|

The most polyphagous insect herbivore? Host plant associations of the Meadow spittlebug, Philaenus spumarius (L.)

Vinton Thompson,
Claire Harkin,
Alan J. A. Stewart

Abstract: A comprehensive list of all known host plant species utilised by the Meadow Spittlebug (Philaenus spumarius (L.)) is presented, compiled from published and unpublished sources. P. spumarius feeds on 1311 host plants in 631 genera and 117 families. This appears, by a large margin, to be the greatest number of host species exploited by any herbivorous insect. The Asteraceae (222 species) and Rosaceae (110) together account for 25% of all host species. The Fabaceae (76) and Poaceae (73), are nearly tied for third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 146 publications
(207 reference statements)
1
7
0
Order By: Relevance
“…Finally, although P. spumarius had the highest generality score at the plant species level, it was not significantly more generalist than A. alni, L. coleoptrata or Neophilaenus sp. The 18 plant families on which it was found in the present study were also reported by Thompson et al (2023). However, we observed P. spumarius on 6 plant genera not yet reported in the literature -namely Anacyclus, Carthamus, Cota, Petrorhagia, Thrincia and Thyrimnus -and 30 new plant species records (see Table S10.1 & S10.2 in Appendix 10).…”
Section: Most Xylem Feeders Are Generalistssupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, although P. spumarius had the highest generality score at the plant species level, it was not significantly more generalist than A. alni, L. coleoptrata or Neophilaenus sp. The 18 plant families on which it was found in the present study were also reported by Thompson et al (2023). However, we observed P. spumarius on 6 plant genera not yet reported in the literature -namely Anacyclus, Carthamus, Cota, Petrorhagia, Thrincia and Thyrimnus -and 30 new plant species records (see Table S10.1 & S10.2 in Appendix 10).…”
Section: Most Xylem Feeders Are Generalistssupporting
confidence: 83%
“…• Cyperaceae, represented by Carex hirta and • Euphorbiaceae represented by Euphorbia helioscopia. Table S10.1 -Plant genera listed in Thompson et al (2023) and in the present study as hosts of P. spumarius. Taxonomy follows the currently accepted names in GBIF (GBIF.org, 2023) after check with 'get_gbif_taxonomy » function in R (Schneider, 2018).…”
Section: Appendix 4: Generalized Linear Mixed Models Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylella fastidiosa is widely spread in the Americas, but has become a new agricultural threat in Europe since the first detection in Apulia (Italy) in 2013 (EFSA, 2020;Saponari et al, 2013). It is able to infect more than 600 plant species among ornamentals, crops and wild plants (European Food Safety Authority (EFSA) et al, 2021;Thompson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The superfamily Cercopoidea ( Hemiptera , Auchenorrhyncha ), commonly known as spittlebugs, feed on xylem sap from a variety of plant hosts. Although some are monophagous throughout their lives or only in the nymphal stage, others are known to be very broadly polyphagous as Philaenus spumarius (L.) is known to be the most polyphagous phytophage ( Thompson et al 2023 ). Their colloquial name derives from the distinctive developmental pattern in their nymphal stages, which is characterised by the production of froth or "spittle", presumably as a protective covering.…”
Section: Introductionmentioning
confidence: 99%